Pemahaman Masyarakat Baet dalam Penggunaan Masker untuk Pencegahan Covid 19 - Zurrahmi; Lubis, Syafrina Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The Covid-19 virus is severe for Indonesian citizens nowadays, especially the Baet people, Aceh Besar. It is due to the low awareness of the Baet people towards the implementation of health protocols. In this case, the use of masks is not considered optimal. The public's perception of unimportant masks is the background to the problem. When viewed from the health aspect, masks have an essential role during the Covid-19 pandemic to reduce the spread of Covid -19. This study aims to describe the information on the importance of using masks, which is inversely proportional to the awareness of the Baet people. The research method used by the author is the descriptive qualitative method. The results showed that residents had not realized the importance of using masks in breaking the chain of spreading Covid-19.